1994
DOI: 10.1002/mrd.1080380114
|View full text |Cite
|
Sign up to set email alerts
|

MPF components and meiotic competence in growing pig oocytes

Abstract: Growing pig oocytes (< or = 90 microns in diameter) are unable to resume meiosis in vitro. The objective of our present experiments has been to identify the reasons for meiotic competence in these cells. By comparing histone H1 kinase activity in growing and fully grown oocytes we demonstrate that incompetence is associated with an inability to activate H1 kinase in growing oocytes. Immunoblotting was used to determine whether this kinase inactivity resulted from a lack of either p34cdc2 protein or B-type cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 20 publications
8
55
1
1
Order By: Relevance
“…The incidence of Mil (15%-30%) in smaller size follicles was quite comparable to a host of other reports for this species (Nickson et al, 1993;Yamada et al, 1993;Otoi et al, 2001;Willingham-Rocky et al, 2003). At the same time, the positive impact of larger follicle size in the dog was analogous to findings in other mammals, including the goat (De Smedt et al, 1994;Crozet et al, 1995), pig (Christmann et al, 1994), cow (Lonergan et al, 1994;Pavlok et al, 1997), and horse (Goudet et al, 1997). In fact, the common denominator for all of these species is that oocytes have more capacity to complete nuclear maturation when the host follicle is >2 mm in diameter.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The incidence of Mil (15%-30%) in smaller size follicles was quite comparable to a host of other reports for this species (Nickson et al, 1993;Yamada et al, 1993;Otoi et al, 2001;Willingham-Rocky et al, 2003). At the same time, the positive impact of larger follicle size in the dog was analogous to findings in other mammals, including the goat (De Smedt et al, 1994;Crozet et al, 1995), pig (Christmann et al, 1994), cow (Lonergan et al, 1994;Pavlok et al, 1997), and horse (Goudet et al, 1997). In fact, the common denominator for all of these species is that oocytes have more capacity to complete nuclear maturation when the host follicle is >2 mm in diameter.…”
Section: Discussionsupporting
confidence: 87%
“…MPF activation is regulated by its subunit concentration, intracellular localization and the phosphorylation-dephosphorylation of specific residues (Norbury and Nurse, 1992;Mothk et al, 1998;Abrieu et al, 2001). It has been shown that meiotically incompetent oocytes (i.e., growing or fully grown oocytes obtained from small follicles) are incapable of activating MPF due to the lack of (1) one of the MPF subunits (Chesnel and Eppig, 1995;de Vantéry et al, 1996;Mitra and Schultz, 1996), or (2) upstream regulators driving the cell cycle (Christmann et al, 1994;Dedieu et al, 1998). Mitogen activated protein kinase (MAPK) also has been shown to be associated with events leading to nuclear maturation completion, including microtubule dynamics, spindle assembly, chromosomal condensation and maintaining oocytes at the Mil stage (Kotani and Yamashita, 2002;Sun et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of histone H1 by cellular extracts forms the basis of an assay used to determine the level of MPF activity during meiosis and mitosis [90]. Changes in the level of MPF activity have been found to be similar during maturation of mouse [96,97], rabbit [98], goat [99], cattle [100][101][102] and pig [103][104][105][106][107] oocytes. Numerous studies have found that the level of MPF activity is relatively low at the germinal vesicle stage and steadily increases as meiosis progresses to the first metaphase (M-I) stage.…”
Section: Maturation-promoting Factormentioning
confidence: 99%
“…In support of this hypothesis, incompetent oocytes show very different patterns of both polypeptide synthesis (McGaughey et al, 1979) and protein phosphorylation (Bornslaeger et al, 1988) compared with their competent counterparts. Moreover, although some MPF proteins are present in meiotically incompetent growing pig oocytes, they are incapable of being activated until the oocyte is fully grown (Christmann et al, 1993).…”
Section: Cell Cycle Proteins and Meiosismentioning
confidence: 99%